Universidad y pensamiento crítico: intelectuales e influencers - Cuadra, Alvaro (Re-presentaciones: Periodismo, comunicación y sociedad, 2021)
In this article we analyze the condition of intellectual and the critical thinking in our present. For this we propose to examine the condition of the poets from the end of XIX century, like Darío and Martí, in view of advent of modern journalism. The performative orientation of the higher education, as much as the interruption and the expansion of OSN (On-line Social Networks) and influencers, are signaled the sunset of this centenary figure: the intellectual.